Morphometry of forage peanut in different development stages - Silva, Marcelo Alves; Berber, Rodolfo Cassimiro de Araujo; Bona filho, Amadeu; Pizarro, Esteban; Munhoz, Alexandre Lucas; Silveira, Fabio Henrique Rodrigues; Cavalheiro, Tatiana; Furini, Pâmela Michéli (Comunicata Scientiae, 2012)
The forage peanut is a plant used as animal food in crop-pasture system. Thus, the objective of this work was evaluated the forage peanut morphometry specie Arachis pintoi cv Belmonte (BRA 031828) in different development stage (dossel height of 5, 10, 20, 30 and 40 cm). The parameters evaluated were: dry matter yield, branch length, average of internodes length, numbers of internodes per branch, leaves per branch and leaf/stem ratio. No differences were found in number of leaves per branch, but leaf/stem ratio was different between 5 and 30 cm and, 5 and 40 cm (P<0.05). The average of dry matter increased exponentially and branch length and internodes length increased in straight line (P<0.05). Above 10 cm no statistics difference were found between number of internodes per branch and the distance between internodes. In short, data this experiment indicated that the dossel height after 10 cm occurred by branch development and increase of distance between internodes and, even had observed changes of dry matter production according to height cut, no differences were observed in leaves per branch.